Acconci, Broodthaers, Calle, Carrión y Fahalström: de la ambliopía a los ambigramas - Parra-Bañón, José J. (Arte, Individuo y Sociedad, 2023)
Reseña de: Verónica Gerber Bicecci. (2021). Mudanza. Bilbao: Casoni. 100 pp. ISBN: 978-84-16205-69-1